Desetletje gibal 2000-2010 - Komadina, Radko (Zdravstveno varstvo, 2002)
Musculo-sceletal conditions are crippling diseases that are the most common causes of severe long-term pain and physical disability, affecting hundreds ofmillions of people across the world. The extent of human suffering is expected to worsen as people live longer and the number of accidents increases. Resulting health problems will cause significant economic burden, escalating the amount of money thatgovernments will need to spend and potentially denying patients the right to necessary treatments and rehabilitation.
Keywords: bolezni; Epidemiology; gibala; Health education; Hospitalizacija; Hospitalization; Mišičnoskeletne bolezni; Mortality; Musculoskeletal diseases; Rehabilitation; Svetovna zdravstvena organizacija; World health organization; Zdravstvena vzgoja